Performance and economic considerations in augmentation of solar still efficiency using solar heat collector coupling - Sonia Z. Issaq; Shamil K. Talal; Aasim A. Azooz (Desalination and Water Treatment)
The literature on the integration of solar heaters with solar stills has sparked considerable debate regarding whether this combination genuinely enhances distillation efficiency. This paper seeks to shed light on this question by examining the daily freshwater yields and thermal efficiencies of four distinct still-heater configurations, each having a total of one-square-meter solar energy collecting area, over several days. These measurements are then compared with the yields and efficiencies of a one-square-meter simple standalone solar still obtained on the same days. The findings reveal that, despite standalone solar stills demonstrating efficiencies ranging from 35% to 45% on days with total daily solar radiation exceeding 6 kW/m2, none of the four still-heater configurations achieved comparable efficiencies on days with solar radiations below approximately 6.7 kW/m2. Notably, the efficiencies of the standalone still were consistently higher than those of all four configurations on days with solar radiation below 6.7 kW/m2. Furthermore, economic analysis indicates that standalone solar stills are more cost-effective to construct than still-heater systems with equivalent solar radiation collecting areas.